2016
DOI: 10.4238/gmr.15038617
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aneuploidies in spontaneous abortions by quantitative fluorescent PCR with short tandem repeat markers: a retrospective study

Abstract: Approximately 10-15% of all pregnancies end in spontaneous abortions. Many factors can lead to embryonic loss; however, it has been well established that over 50% of all miscarriages result from chromosomal abnormalities, primarily aneuploidies (>96%). Identifying the cause of miscarriage can significantly reduce the psychological stress in women, and enable better genetic counseling for a future pregnancy. Quantitative fluorescent polymerase chain reaction (QF-PCR) has been previously used in the study of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…These results corroborate with other studies that demonstrated similar results, showing that trisomies, especially those involving chromosomes 16 and 22, are implicated in spontaneous abortion. 17,[20][21][22][23][24][25] An important point noted in the present study was that trisomy 15 was found in 8. Conventional cytogenetics technique remains highly recommended for spontaneous miscarriage analysis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These results corroborate with other studies that demonstrated similar results, showing that trisomies, especially those involving chromosomes 16 and 22, are implicated in spontaneous abortion. 17,[20][21][22][23][24][25] An important point noted in the present study was that trisomy 15 was found in 8. Conventional cytogenetics technique remains highly recommended for spontaneous miscarriage analysis.…”
Section: Discussionmentioning
confidence: 78%
“…However, this method has certain disadvantages, such as a long laboratory cycle, labor intensity and culture failure, especially when the tissues obtained from patients are not well preserved. 17,26 The QF-PCR technique is regarded as a highly accurate, low cost and rapid diagnostic method to facilitate the detection of clinically relevant chromosome aberrations. However, some limitations of the technique are the difficulty to offer a correct diagnosis for mosaicism, small deletions, translocations and duplications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical miscarriage can be further divided into early clinical miscarriage, which occurs before the twelfth week of gestation or late clinical miscarriage, which occurs between the twentieth and twenty-first week of pregnancy. The incidence of early clinical miscarriage is about 15%, with considerable variation depending on maternal age [2,3]. For women aged 20 to 24 years, the incidence of early clinical miscarriage is 10%, but it rises to 51% among women aged 40 to 44 years [4].…”
Section: Introductionmentioning
confidence: 99%
“…В связи с этим, учитывая высокую стоимость данных исследований, стандартное кариотипирование НБ/СА остается наиболее доступным, рутинным и довольно информативным трисомии [11] в мировой литературе описано всего 456 наблюдений (в отечественной литературе подобных отдельных публикаций прежде не было) [25,26,[43][44][45][46]. Различные исследователи, изучавшие эту патологию, отметили, что двойные и множественные трисомии ассоциируют с более старшим возрастом матери по сравнению с регулярными трисомиями по одной хромосоме, анэмбрионией и морфологическими дефектами эмбрионов по результатам УЗИ и более ранним сроком репродуктивных потерь [47].…”
unclassified